Successful autologous CD19 CAR T cell therapy following severe lupus flare during immunosuppressive washout in refractory lupus nephritis - Gerber, Jonathan M.; Dehdashtian, Ehsan; Hu, Guangnan; Gregoire, Cara; Borie, Dominic; Bindal, Poorva; Cerny, Jan; Geara, Abdallah; Schett, Georg; Caricchio, Roberto (2025)
Objective To evaluate the safety and efficacy of CD19 chimeric antigen receptor (CAR) T cell therapy in a patient with refractory lupus nephritis who experienced severe disease flare during immunosuppressive washout, and to assess whether pulse corticosteroid intervention affects CAR T cell therapeutic outcomes. Methods We report a single case of a 22-year-old woman with SLE and lupus podocytopathy refractory to multiple therapies including rituximab, belimumab and obinutuzumab. The patient was treated under single-patient IND (#30146) with autologous CD19 CAR T cells (KYV-101). During the preinfusion washout period, she developed severe lupus flare requiring pulse intravenous methylprednisolone. Clinical outcomes, CAR T cell expansion, B cell depletion and laboratory parameters were monitored before and after therapy. Results Despite experiencing severe lupus flare (fever, rash, arthritis, anti-dsDNA elevation, hypocomplementaemia) during washout, pulse methylprednisolone (250mg intravenous, rapidly tapered) successfully controlled symptoms without compromising subsequent CAR T cell expansion (peak 15.5cells/µL on day 7). The patient achieved sustained clinical remission with SLE Disease Activity Index Score decreasing from 17 prior to leukapheresis to 4 by week 17. At 12 months postinfusion, she remained in drug-free remission with stable kidney function and had returned to full-time work. Conclusion This case report illustrates that targeted pulse corticosteroids during CAR T cell therapy washout can effectively manage severe lupus flares without impairing therapeutic efficacy.
CRIS-Team Scopus Importer:2025-12-05
Keywords: Glucocorticoids; Lupus Erythematosus; Systemic; Lupus Nephritis